Studi Literatur Tentang Implementasi Kebijakan Pemerintah Dalam Peningkatan Keselamatan Transportasi Laut - Agnesi, Sarah Ghea; Wirza, Elfira (Jurnal Cakrawala Bahari, 2025)
Maritime transportation safety is a crucial aspect in supporting maritime efficiency, sustainability, and competitiveness. This study aims to analyze the implementation of government policies to improve maritime transportation safety through a literature review of various journals, international reports, and policy documents over the past five years. The study results indicate that policy effectiveness is influenced by four main factors: regulatory alignment with international standards, institutional effectiveness in supervision, utilization of technology and innovation, and strengthening a safety culture. Although Indonesia has adopted global standards such as SOLAS, MARPOL, and the ISM Code, their implementation still faces challenges such as weak oversight, low compliance, and limited cross sectoral coordination. The study's conclusions emphasize the need for an integrated approach that integrates regulation, technology, and safety culture with the support of evidence-based policies. National and international collaboration is key to realizing a safe maritime transportation system while contributing to sustainable maritime development.